Agricultural public spending in Nigeria - Mogues, Tewodaj; Morris, Michael L.; Freinkman, Lev; Adubi, Abimbola; Ehui, Simeon; Nwoko, Chinedum; Taiwo, Olufemi; Nege, Caroline; Okonji, Patrick; Chete, Louis (International Food Policy Research Institute, 2008)
Public spending on agriculture in Nigeria is exceedingly low. Less than 2 percent of total federal expenditure was allotted to agriculture during 2001 to 2005, far lower than spending in other key sectors such as education, health, and water. This spending contrasts dramatically with the sector's importance in the Nigerian economy and the policy emphasis on diversifying away from oil, and falls well below the 10 percent goal set by African leaders in the 2003 Maputo agreement. Nigeria also falls far behind in agricultural expenditure by international standards, even when accounting for the relationship between agricultural expenditures and national income. The spending that is extant is highly concentrated in a few areas. Three out of 179 programs account for more than 81 percent of federal capital spending, of which nearly three-quarters go to government purchase of agricultural inputs and agricultural outputs alone. The analysis finds that many of the Presidential Initiatives-which differ greatly in target crops, technologies, research, seed multiplication, and distribution-have identical budgetary provisions. This pattern suggests that the needs assessment and costing for these initiatives may have been inadequate, and that decisions may have been based on political considerations rather than economic assessment. Budget execution is also poor. The Public Expenditure and Financial Accountability (PEFA) best practice standard for budget execution is no more than 3 percent discrepancy between budgeted and actual expenditures. In contrast, during the period covered by the study, the Nigerian federal budget execution averaged only 79 percent, meaning 21 percent of the approved budget was never spent. Budget execution at the state and local levels was even less impressive, ranging from 71 percent to 44 percent. However, other sectors showed similar low levels of budget execution, suggesting that the problem is a general one going beyond agriculture. There is an urgent need to improve internal systems for tracking, recording, and disseminating information about public spending in the agriculture sector. Consolidated and up-to-date expenditure data are not available within the Ministry of Agriculture, not even for its own use. Without this information, authorities cannot undertake empirically-based policy analysis, program planning, and impact assessment. There is also a need for clarification of the roles of the three tiers of government in agricultural services delivery. This is important to reduce overlaps and gaps in agricultural interventions and improve efficiency and effectiveness of public investments and service delivery in the sector. Finally, applied research is needed to address critical knowledge gaps in several areas: (i) Spending on fertilizer programs makes up a sizeable portion of overall agricultural spending in Nigeria, yet very little is known about the impact of this spending. (ii) To date, only a small portion of the national grain storage system has been constructed, but if the entire network is completed as planned, the cost will be enormous. Supporting even the current modest level of grain marketing activities is consuming significant amounts of public resources. Is an investment on this order of magnitude desirable? What has been the impact of these investments? (iii) There is a need for an analytical study focusing on the economics of the National Special Program for Food Security (NSPFS). The total cost of NSPFS II is estimated at US$364 million. Detailed financial information about the NSPFS is not publicly available, however, making it difficult to assess whether the considerable investment in NSPFS I generated attractive returns, and whether NSPFS II merits support as currently designed. A rigorous external evaluation is needed to assess the performance of NPSFS and generate information that could be used to make design adjustments. --Authors' Abstract